THE EFFECT OF BLADE NUMBER AND WATER VELOCITY TOWARD THE PERFORMANCE OF HELIKS GORLOV TURBINE - Jeri Pranio; Karnowo Karnowo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2019)
This study was aimed at determining the influence of the number of blades and water velocity on the performance of vertical axis water turbine type Helical Gorlov. The method used was an experimental method. The descriptive analysis method was also used to analyze the data. The data obtained were in the form of variations of blades number and water velocity. The variations in the number of blades used were 2 blades, 3 blades, and 4 blades. While water velocity variations used were 0.81 m / s, 0.94 m / s, 1.08 m / s, and 1.18 m / s. The parameters were used to measure the amount of current and voltage produced by the multimeter and the number of rotations per minute (rpm) of the turbine produced by the tachometer. The results show that the number of blades and water velocity affected the performance of the Gorlov helical water turbine. The most optimal Gorlov helical turbine based on the results of research with the highest power coefficient (Cp) value is a turbine with 2 blades at a water velocity of 0.94 m/s which produces a Cp value of 0.00376 and a TSR value of 1.35.PENGARUH JUMLAH SUDU DAN KECEPATAN AIR TERHADAP KINERJA TURBIN AIR SUMBU VERTIKAL TIPE HELIKS GORLOVPenelitian ini bertujuan untuk pengaruh jumlah sudu dan kecepatan air terhadap kinerja turbin air sumbu vertikal tipe Heliks Gorlov. Metode yang digunakan dalam penelitian ini adalah eksperimen. Penelitian ini menggunakan analisis deskriptif.Data yang duperoleh berupa variasi jumlah sudu dan variasi kecepatan air. Variasi jumlah sudu yang digunakan adalah 2 sudu, 3 sudu, dan 4 sudu. Variasi kecepatan air yang digunakan yaitu 0,81 m/s, 0,94 m/s, 1,08 m/s, dan 1,18 m/s. Parameter dalam penelitian ini yang digunakan untuk menentukan kinerja adalah mengukur besarnya arus dan tegangan yang dihasilkan multimeter dan banyaknya rotasi per menit (rpm) dari turbin yang dihasilkan tachometer.Hasil penelitian menunjukkan bahwa jumlah sudu dan kecepatan air mempengaruhi kinerja turbin air heliks gorlov. Kedua, kecepatan air mempengaruhi kinerja turbin air heliks gorlov.Turbin heliks Gorlov paling optimal berdasarkan hasil penelitian dengan nilai koefisien daya (Cp) tertinggi yaitu turbin dengan 2 sudu pada kecepatan air 0,94 m/s yang menghasilkan nilai Cp sebesar 0,00376 dan nilai TSR 1,35.